Pulmonary hypertension in chronic heart failure: definitions, advances, and unanswered issues. (20th July 2018) - Berthelot, Emmanuelle; Bauer, Fabrice; Eicher, Jean‐Christophe; Flécher, Erwan; Gellen, Barnabas; Guihaire, Julien; Guijarro, Damien; Roul, Gérald; Salvat, Muriel; Tribouilloy, Christophe; Zores, Florian; Lamblin, Nicolas; et al.
Abstract: Pulmonary hypertension (PH) is a common and severe complication of heart failure (HF). Consequently, HF is the leading cause of PH. For many years, specialists have attempted to better understand the pathophysiology of PH in HF, to define its prevalence and its impact on prognosis in order to improve the therapeutic management of these patients. Nowadays, despite the recent guidelines published on the subject, several points remain unclear or debated, and until now, no study has demonstrated the efficacy of any treatment. The aim of this review is to report the evolution of the concepts on post‐capillary PH (diagnosis, prevalence, prognosis, and therapeutics). The main issues are raised, focusing especially on the link between structural alterations and haemodynamic abnormalities, to discuss the possible reasons for treatment failures and future potential targets.